Information Support of Foreign Policy - O. A. Melnikova (Vestnik MGIMO-Universiteta, 2015)
Informatization and modern information technologies cover the most various areas of social, spiritual and material human life and have become the dominating globalization factor with major impact on world events. Modern international relations present new challenges and threats ofcross-border nature, which fall within the area of information security. This brings issues of informational influence on international policy to the fore. In this context the question of improvement and modernization of policy instruments for more effective use of modern means of implementation of foreign policy priorities, including information support of international activities, achieves fundamental importance. Given the complexity of modern international relations and tasks facing foreign affairs departments, diplomatic success in many cases depends onthe efficiency of information support. The article analyses current objectives and methods of information support of foreign policy in the context of modern Russian legislation. The author examines the approach of the Information and Press Department of the Russian Ministryof Foreign Affairs,a subdivision responsible for information support and international cooperation in the media sphere. The article specifies the key role of new information technologies for informing the audience expeditiously and to the full extent in regard to Russian approaches to the solution of international problems, foreign policy initiatives and actions of the Russian Federation, and for counteracting attempts to discredit Russian foreign policy.